â€œInterferences in Translation.â€ English Applied Linguistics Study Program, Postgraduate school State University of Medan, 2016 - Sinaga, Arman Bemby (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2018)
The objectives of the study are (1) to describe the types of interference which occurred in the translation of bilingual books, (2) to investigate the process of interference occurred in the translation of bilingual children reading books, and (3) to state the reason for linguistic interferences occurrence in the translation of bilingual books. This research uses qualitative research method especially the applied theory. The source of the data is the translated books â€œSeri HewanTerâ€ published by Kids Bestari (2014). The data area analyzed based on Bogdan and Biglenâ€™s stages/steps especially searching the data, arranging the data and interpreting. The validity of the is taken by applying investigator triangulation involves multiple data sources in an investigation to produce understanding. Based on the analysis, it is found that there are two kinds of interferences found they are (1) syntactical interference and (2) lexical interference. The syntactical interference consisted of omission interferences (28), misorder interferences (9) and misformation interferences (73). Then, lexical interference (45) consisted of pronominal interferences (30) and redundancy interferences (15).